2019
DOI: 10.3390/ijms20194962
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Targeting of GLUT1 to Control Autoreactive T Cell Responses

Abstract: An increasing body of evidence indicates that bio-energetic metabolism of T cells can be manipulated to control T cell responses. This potentially finds a field of application in the control of the T cell responses in autoimmune diseases, including in type 1 diabetes (T1D). Of the possible metabolic targets, Glut1 gained considerable interest because of its pivotal role in glucose uptake to fuel glycolysis in activated T cells, and the recent development of a novel class of small molecules that act as selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…Several inhibitors of glycolysis have been developed over the years, including 2-deoxiglucose. More recently, a novel class of small molecules displaying high selectivity against glucose transporter 1 (Glut1) and with good pharmacokinetic and pharmacodynamic characteristics have been produced [ 7 ]. The pharmacological blockade of Glut1 is therefore a promising strategy to boost both a long-lasting immune response and reduce tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Several inhibitors of glycolysis have been developed over the years, including 2-deoxiglucose. More recently, a novel class of small molecules displaying high selectivity against glucose transporter 1 (Glut1) and with good pharmacokinetic and pharmacodynamic characteristics have been produced [ 7 ]. The pharmacological blockade of Glut1 is therefore a promising strategy to boost both a long-lasting immune response and reduce tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…A novel Th17 antibody‐modified liposome polycation‐DNA complex (LPD) containing encapsulated siRNA against TSPAN1 (Th17‐LPDT) was reported to inhibit the development of gastric cancer by decreasing the polarization of CD4 + T cells (Lu et al, 2020). SLC2A1 is a major glucose transporter in mammalian cells and was also demonstrated to be closely associated with the immune response, including the activation and differentiation of T cells, as well as the glucose metabolism of macrophages and inflammation (Di Dedda et al, 2019; Freemerman et al, 2019). In addition, previous research identified that PPARGC1A and GPRC5A play a role in immunity and inflammation (Jing et al, 2020; Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…T-cells have a cytoplasmic pool of Glut1 that are transported to the cell surface following activation and is linked closely to a peak in glucose uptake between 48 to 72 h post activation 29,30 . If Glut1 is blocked, the capacity of proliferating naïve T-cells to transform into TSCM is severely compromised.…”
Section: Applications Of a Simple Unstructured Ode Model On T-cell Growth And Phenotypic Commitmentmentioning
confidence: 99%
“…However, as a new therapeutic class based on a relatively unexplored bioprocess input material, primary T-cells manufacturing technology is particularly immature 3 . The knowledge of process control and its impacts on product quality, such as population distributions and yield, are significantly understudied relative to more established biopharmaceuticals 5 . This lack of knowledge restricts the opportunity for operational optimisation that might drive down costs and/or create more consistent product 6 .…”
Section: Introductionmentioning
confidence: 99%